Regivärsist üldse ja vepsa regivärsist eriti - Ülo Tedre (Mäetagused, 2015)
The article about the runic verse in general and Vepsian runic verse in particular weighs the reasons why the Veps and especially southern Estonians preserved their song material, yet could not achieve the form of the runic verse.